THE STRATEGY OF THE HEAD OF THE QUR'AN EDUCATION PARK IN IMPROVING STUDENT ACHIEVEMENT - Zunaida, Laily; Aulia, Maulidiah Amirul (Jurnal Inovatif Manajemen Pendidikan Islam, 2023)
This study discusses the strategy of the head of the Hafidzul Qur'an Al-Bukhori Quran Education Park (TPQ) in improving student achievement amidst the challenges of globalization. The focus is on describing the strategic steps and keys to success in implementing the strategy. This study uses a qualitative case study approach with observation, interview, and documentation techniques. The main findings show that the steps taken include monthly training for asatidzah, holding competitions every few months, and special learning for students who will participate in the competition. The keys to success of this strategy include adequate financial support, motivation and moral support from parents, and facilities that allow students to develop their potential to the maximum. This strategy is expected to be able to improve student achievement at TPQ Hafidzul Qur'an Al-Bukhori.